The Role of Islamic Religious Education Teachers in Fostering Student Learning Discipline at SMK N 1 Pekalongan - Listiyanti, Galuh; Aziz Q, Ihwan; Hasyim, Umar Alfaruq A. (CV. BImbingan Belajar Assyfa, 2024)
Student discipline is very important for the progress of the school itself. An orderly school will create a good learning process. However, on the other hand, in less orderly schools the conditions will be much different and the learning process will be less effective. Improving discipline towards students is very important for schools, considering that schools are the place for the nation's next generation. Discipline is very necessary in schools to become reliable mental formation institutions. Without the value of discipline, schools will only become places where various kinds of conflicts can arise so that chaos can occur due to disciplinary actions. The aim of the research that the author wants to carry out is to find out the role of Islamic Religious Education teachers in fostering learning discipline in class X TKR students at SMK N 1 Pekalongan, East Lampung Regency. To obtain concrete data in field research, the research design in this study used qualitative descriptive research. In the course of collecting data the author used observation, interviews and documentation methods. Meanwhile, in analyzing, the author uses qualitative descriptive analysis techniques. To support the description of the situation in the field, the author includes documentation to complement and strengthen the research data. The results of this research show that after conducting research, the role of PAI teachers was found, namely as an educator, tutor, leader, mentor, motivator, coordinator, evaluator and also as a role model. With this role, teachers instill the character of discipline and responsibility in children when learning in class and in other school activities outside the classroom.